2017
DOI: 10.1002/2017jc013204
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian‐Based System to Assess Wave‐Driven Flooding Hazards on Coral Reef‐Lined Coasts

Abstract: Many low‐elevation, coral reef‐lined, tropical coasts are vulnerable to the effects of climate change, sea level rise, and wave‐induced flooding. The considerable morphological diversity of these coasts and the variability of the hydrodynamic forcing that they are exposed to make predicting wave‐induced flooding a challenge. A process‐based wave‐resolving hydrodynamic model (XBeach Non‐Hydrostatic, “XBNH”) was used to create a large synthetic database for use in a “Bayesian Estimator for Wave Attack in Reef En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
142
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(165 citation statements)
references
References 45 publications
(91 reference statements)
5
142
0
Order By: Relevance
“…The exception was the rough run with the lowest wave height ( H rms , SS ,0 = 0.03 m), which demonstrated a higher contribution from setup due to the very weak swash motions (see swash spectra in Figure b). These observations are consistent with the numerical simulations of Pearson et al ().…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The exception was the rough run with the lowest wave height ( H rms , SS ,0 = 0.03 m), which demonstrated a higher contribution from setup due to the very weak swash motions (see swash spectra in Figure b). These observations are consistent with the numerical simulations of Pearson et al ().…”
Section: Resultssupporting
confidence: 93%
“…The relative strength of the amplification, inferred from the normalized swash spectral density, of mode 0 for smooth runs appears to have been constant with changes to offshore SS wave height, but increased with both SS peak period and still water depth over the reef flat (Figure ). Previous studies of resonance on fringing reefs have also found that resonant responses can increase with increasing water depth and with lower frequency incident SS waves (Gawehn et al, ; Pearson et al, ; Péquignet et al, ), although in general the natural frequencies and amplification are specific to the reef geometry. The increased resonant amplification was likely due to reduced frictional wave dissipation (Péquignet et al, ) and the forcing (the incident wave groups) becoming closer in frequency to the natural frequencies, which increased with increased water depth.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The offshore bottom elevation is kept at a constant level throughout this study ( z 0 = − 30 m; k peak h < 1.4) and extended in offshore direction in order to let the model adjust to the boundary conditions. The beach extends from the toe upward to a fictitious elevation of z b = 30 m for all simulations, similar to Pearson et al (), in order to focus on runup as a proxy for overtopping (Matias et al, ). Based on Quataert et al (), a distinction is made between the hydrodynamic roughness of the fore reef ( c f = 0.4) and reef flat ( c f = 0.01) due to characteristic differences in coral reef structure (live/branching coral at the fore reef and deposited/cemented coral sands and fragments on the reef flat and beach).…”
Section: Methodsmentioning
confidence: 99%
“…A number of parameters were varied to create a large set of artificial reefs with different geometries (Table ), following the approach of Pearson et al (), Pomeroy, van Dongeren, et al (), and Quataert et al (). The presented parameters were selected based on a sensitivity analysis that assessed the impact of each parameter on reef hydrodynamics and on the effects of excavation pits (Klaver, ), as well as on the results of previous research on fringing reef hydrodynamics and wave runup (Pearson et al, ; Quataert et al, ). Wave runup and subsequent flooding of reef‐lined coasts is influenced most by hydrodynamic forcing, fore reef slope, reef width, reef submergence, and beach slope (Pearson et al, ; Quataert et al, ; Shimozono et al, ).…”
Section: Methodsmentioning
confidence: 99%